Multiphoton nonclassical light from clusters of single-photon emitters. (6th July 2018) - Qi, Luo; Manceau, Mathieu; Cavanna, Andrea; Gumpert, Fabian; Carbone, Luigi; Vittorio, Massimo de; Bramati, Alberto; Giacobino, Elisabeth; Lachman, Lukas; Filip, Radim; Chekhova, Maria
Abstract: We study nonclassical features of multiphoton light emitted by clusters of single-photon emitters. As signatures of nonclassicality, we use violation of inequalities for normalized correlation functions of different orders or the probabilities of multiphoton detection. In particular, for clusters of 2–14 colloidal CdSe/CdS dot-in-rods we observe antibunching and nonclassicality of up to the fourth-order. Surprisingly, violation of certain classical inequalities gets even more pronounced for larger clusters.